2014
DOI: 10.1016/j.exger.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial quality control and age-associated arterial stiffening

Abstract: Stiffening of large elastic arteries with age increases the risk of cardiovascular diseases (CVD), but the underlying mechanisms are incompletely understood. We investigated the role of mitochondrial quality control (QC, i.e., mitophagy and biogenesis) in arterial stiffening with aging. In C57BL6 mice, aging was associated with impaired aortic expression of mitochondrial QC mediators, greater activation of the mitochondrial redox/stress sensor p66shc, elevated superoxide production and increased arterial stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 24 publications
8
65
0
Order By: Relevance
“…[100] 13 Trehalose, a neutraceutical that enhances mitophagy, was reported to reverse agerelated arterial stiffening of the aorta and pulse wave velocity when given as a food supplement to old mice. [101] This study inferred and supported the notion that mitochondrial stress/dysfunction during aging underlies age-related aortic stiffening, possibly in the presence of oxidative stress and inflammatory cytokines. Thus, trehalose and similar non-reducing disaccharides, could lower free radical production and pulse wave velocity while normalizing the over-produced aortic collagen I, a key contributor to age-associated arterial stiffness.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…[100] 13 Trehalose, a neutraceutical that enhances mitophagy, was reported to reverse agerelated arterial stiffening of the aorta and pulse wave velocity when given as a food supplement to old mice. [101] This study inferred and supported the notion that mitochondrial stress/dysfunction during aging underlies age-related aortic stiffening, possibly in the presence of oxidative stress and inflammatory cytokines. Thus, trehalose and similar non-reducing disaccharides, could lower free radical production and pulse wave velocity while normalizing the over-produced aortic collagen I, a key contributor to age-associated arterial stiffness.…”
supporting
confidence: 82%
“…Thus, trehalose and similar non-reducing disaccharides, could lower free radical production and pulse wave velocity while normalizing the over-produced aortic collagen I, a key contributor to age-associated arterial stiffness. [101,102] (Fig. 2) Downstream, trehalose also acts as an antioxidant and free radical scavenger.…”
mentioning
confidence: 99%
“…Despite relatively low abundance [64] and minimal respiratory activity [1012], arterial mitochondria play a vital role in maintaining arterial function, presumably via other roles involving intra- and extra-cellular signaling [1012, 15]. However, arterial mitochondrial health and quality control decline with aging and in disease models of hypertension, NO deficiency, atherosclerosis, diabetes and metabolic syndrome [1314, 2729, 41, 4445]. In the present study we observed age-related declines in PGC-1α and SIRT3, key regulators of mitochondrial biogenesis, health and antioxidant defenses [2122, 39], as well as a shift in mitochondrial dynamics favoring increased mitochondrial fission (e.g., increased Fis1 and decreased Mfn2), a characteristic of mitochondrial dysfunction [41, 4446].…”
Section: Discussionmentioning
confidence: 99%
“…A key source of arterial oxidative stress is excessive production of mitochondrial reactive oxygen species (mtROS). Whereas healthy mitochondria are critical mediators of arterial homeostasis [1014] and produce physiological levels of mtROS vital for cell signaling [15], declines in mitochondrial health are characterized by excessive mtROS production [1012, 1516]. We have recently shown that excess arterial mtROS production is a major contributor to tonic arterial oxidative stress-mediated suppression of EDD with primary aging in mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several naturally occurring nutraceuticals may have the potential to boost autophagy. For example, oral supplementation with trehalose, a disaccharide found in mushrooms and honey, stimulates autophagy and reverses endothelial dysfunction and arterial stiffening in old mice by normalizing oxidative stress and structural proteins, while also ameliorating vascular inflammation (LaRocca et al, 2014; LaRocca et al, 2012). The autophagy enhancer spermidine (a polyamine found in grapefruits and fermented soy products) also enhances arterial autophagy and reverses age-associated endothelial dysfunction and arterial stiffness in mice (LaRocca et al, 2013).…”
Section: Nutritional Factors and Interventionsmentioning
confidence: 99%